Processo formativo de egressos do doutorado em Educação em Ciências e Matemática da REAMEC : autoavaliação do programa com a segunda turma (2013) - Nascimento Filho, Virgílio Bandeira do (2022)
The present research analyzes the formative process of egress graduates of the second class (2013) of the doctorate in Science and Mathematics Education at PPGECEM/REAMEC, through the study of formation trajectories, as well as the products of this formation and the impact on the personal, institutional and professional lives of these graduates. As a research problem, this question: how does REAMEC promote changes in the professional trajectory of university teaching for graduates? The objective of the research was to analyze the formative process of PPGECEM / REAMEC and identify the impacts of the program for the teaching of Science and Mathematics in the Brazilian Legal Amazon area with the collaboration of the second class (2013) of graduates of the course, in an emancipatory way. The research is quali-quantitative, having as research subjects the 44 graduates of the second group of doctors graduated by PPGECEM / REAMEC: at first, a documentary was made of the Lattes Curriculum of the graduates of the class that joined the program in 2013 (with 100% concluded the process), which served as a basis for analysis of understanding and characterization of the profile of the second class; in a second moment, all 44 graduates were sent a questionnaire that was produced on the Google Docs Platform, with a return of 22 (50%) questionnaires; in a third stage, a focus group was held with the participation of 7 graduates who were willing to collaborate with the research. Quantitative data were analyzed by mean, median and percentage and represented in graphs and tables. Qualitative data (open questions of the questionnaire and focus group) were analyzed using the Discursive Textual Analysis (DTA) technique. The analysis allowed 1) to profile the graduates of the second group, describing the impact of the program on their personal, professional and institutional lives; 2) to relate strengths and weaknesses of the program in development in the ALB, in collaboration with the graduates of the second class of PPEGECEM / REAMEC, through emancipatory evaluation. With this, we defend the following thesis: The formative process of the Postgraduate Programme in Education in Science and Mathematics of the Amazonian Network of Education in Science and Mathematics has contributed to the personal, professional and institutional development of the graduated doctors and the monitoring of these graduates through self-assessment may contribute to the improvement of the programme aiming at excellence.